Hydrothermal synthesis of nano-sized MnO2 supported on attapulgite electrode materials for supercapacitors. (5th April 2023) - Lin, Tao; Lin, Jiacheng; Wei, Xiaoyao; Lu, Lulu; Yin, Xuefeng
Abstract: Among the electrode materials of supercapacitors, transition metal oxides have been widely used because of their low price, high theoretical capacitance and good cycle stability, and MnO2 is one of the typical representative materials. However, the actual specific capacitance of MnO2 is low because of its poor conductivity, easy agglomeration in the preparation process and large volume change in the process of repeated charge and discharge. Attapulgite can not only provide a large specific surface area for transition metal oxide materials, but also provide a skeleton on which nano-sized materials can be grown or dispersed. Therefore, the electrochemical performance of electrode materials can be improved by designing nanostructures and compounding a variety of materials with different properties. Herein, a new type of composites electrode material is prepared by simple one-step hydrothermal method. As an electrode material, the ATP-MnO2 composites exhibited a high specific capacitance of 138.2 F/g at a current density of 0.5 A/g, which was 13.4% higher than that of pure MnO2 nanoflowers. Under the current density of 3 A/g, the capacitance retention of ATP-MnO2 composites was 89.4% after 5000 cycles. Highlights: Provides a new idea for the application of clay-based materials in electrochemistry. Composites can be prepared by a simple hydrothermal method. Attapulgite can disperse the agglomeration of MnO2 and improve the adsorption. The capacitance and cyclic stability of the composites can be improved by attapulgite.